Formulation and evaluation of oral sustained release of Diltiazem Hydrochloride using rosin as matrix forming material - Lakshmana Prabu, S.; Shirwaikar, AA; Shirwaikar, A; Ravikumar, G; Kumar, A; Jacob, A (Ars Pharmaceutica (Internet), 2009)
Rosin, a natural resin, was used as a hydrophobic matrix material for the controlled release, using diltiazem HCl as model drug. Matrix tablets were prepared by direct compression method using rosin as matrix forming material in different proportions and with different diluent combinations. The tablets prepared were flat faced, retained their shape throughout. The method of preparation of matrix system and its concentration were found to have pronounced effect on the release of diltiazem HCl. The release was found to follow both the first order kinetics and fickian diffusion. The drug delivery was analyzed using the paddle method according to USP XXIII. All the studies were done in phosphate buffer pH 7.4. The matrix tablets were evaluated for its thickness, hardness, friability, weight variation, drug content and invitro release studies. The results suggest that the rosin is useful in developing sustained release matrix tablets, prolong release of water soluble drug for up to 24h. Rosin thus promises considerable utility in the development of oral sustained release drug delivery systems.